1981
DOI: 10.1111/j.1471-4159.1981.tb00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Inhibition of Rat Brain Monoamine Oxidase In Vitro by MD780515

Abstract: The inhibiton of type A and B MAO in rat forebrain crude membrane preparation by MD780515, (3-(4-[(3-cyanophenyl)methoxy]phenyl)-5-(methoxymethyl)-2-oxazolidinone-Centre de Recherche Delalande, France) has been investigated in vitro with 5-hydroxytryptamine and beta-phenylethylamine as substrates. The inhibition of the high-affinity binding of [3H]harmaline, a specific marker of type A MAO, was also studied. In the experimental conditions used, MD780515 appeared to be a pure mixed MAO inhibitor (MAOI) of 5-HT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…6-Phenethylamine was metabolised by MAO-B, although a small (12-26%, depending on the tissue) component of MAO-A was also found (Table 1). Such a result is consistent with other studies (see, e.g., Kinemuchi et al, 1980;Kan and Strolin Benedetti, 1981;Suzuki et al, 19816) that have demonstrated a considerable MAO-A component of P-phenethylamine oxidation at high substrate concentrations, although the extent of the MAO-A contribution has been overestimated in some cases since P-phenethylamine, at high concentrations, can act as a time-dependent inhibitor of MAO-B activity (Kinemuchi et al, 1981). At a concentration of 50 p M , 80-90% of the dopamine was metabolised by MAO-A, whereas at a concentration of 1000 p M , the contribution of MAO-A was slightly lower (Table 1).…”
Section: J Fowler and M Strolin Benedettisupporting
confidence: 91%
“…6-Phenethylamine was metabolised by MAO-B, although a small (12-26%, depending on the tissue) component of MAO-A was also found (Table 1). Such a result is consistent with other studies (see, e.g., Kinemuchi et al, 1980;Kan and Strolin Benedetti, 1981;Suzuki et al, 19816) that have demonstrated a considerable MAO-A component of P-phenethylamine oxidation at high substrate concentrations, although the extent of the MAO-A contribution has been overestimated in some cases since P-phenethylamine, at high concentrations, can act as a time-dependent inhibitor of MAO-B activity (Kinemuchi et al, 1981). At a concentration of 50 p M , 80-90% of the dopamine was metabolised by MAO-A, whereas at a concentration of 1000 p M , the contribution of MAO-A was slightly lower (Table 1).…”
Section: J Fowler and M Strolin Benedettisupporting
confidence: 91%
“…Catalase activity was determined by monitoring the absorbance of H 2 O 2 at 230 nm (Aebi, 1987). Monoamine oxidase B (MAO-B) activity was determined by detecting the amount of benzylaldehyde at 242 nm (Kan and Benedetti, 1981). Lipid peroxidation was assayed by the measurement of malondialdehyde level on the basis of malondialdehyde reacting with thiobarbituric acid (detected at 532 nm) (Ohkawa et al, 1979).…”
Section: Age-related Enzyme Assaysmentioning
confidence: 99%
“…Early investigations indicated that in the rat brain, 5-hydroxytryptamine (5-HT) is a substrate for MAO-A alone, P-phenethylamine and benzylamine for MAO-B alone, and tyramine for both forms of the enzyme (Johnston, 1968; Yang and Neff, 1973). Recent investigations in the rat brain and liver, however, have indicated that 0-phenethylamine is also a substrate for MAO-A, although the metabolism takes place at a slower rate and with a higher K , value than with MAO-B (Kinemuchi et al, 1979;Suzuki et al, 1979;Tipton and Mantle, 1981;Kan and Strolin Benedetti, 1981;Tipton et al, 1981).In a recent study, it was suggested that 5-HT is a substrate exclusively for MAO-A in the rat striatum (Schoepp and Azzaro, 1981). However, studies in the pig liver and rat liver have suggested that 5-HT is, in fact, metabolised by MAO-B, albeit with a much lower V,,, and a higher K , value than for the A form of the enzyme (Ekstedt, 1979;Tipton and Mantle, 1981;Tipton et al, 1982).…”
mentioning
confidence: 99%
“…Early investigations indicated that in the rat brain, 5-hydroxytryptamine (5-HT) is a substrate for MAO-A alone, P-phenethylamine and benzylamine for MAO-B alone, and tyramine for both forms of the enzyme (Johnston, 1968; Yang and Neff, 1973). Recent investigations in the rat brain and liver, however, have indicated that 0-phenethylamine is also a substrate for MAO-A, although the metabolism takes place at a slower rate and with a higher K , value than with MAO-B (Kinemuchi et al, 1979;Suzuki et al, 1979;Tipton and Mantle, 1981;Kan and Strolin Benedetti, 1981;Tipton et al, 1981).…”
mentioning
confidence: 99%